2017
DOI: 10.1093/mnras/stx512
|View full text |Cite
|
Sign up to set email alerts
|

SCUBA-2 follow-up of Herschel-SPIRE observed Planck overdensities

Abstract: We present SCUBA-2 follow-up of 61 candidate high-redshift Planck sources. Of these, 10 are confirmed strong gravitational lenses and comprise some of the brightest such submm sources on the observed sky, while 51 are candidate proto-cluster fields undergoing massive starburst events. With the accompanying Herschel-SPIRE observations and assuming an empirical dust temperature prior of 34 +13 −9 K, we provide photometric redshift and far-IR luminosity estimates for 172 SCUBA-2-selected sources within these Plan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 46 publications
2
21
0
Order By: Relevance
“…The photometric redshift distribution of all the sources in these 13 candidate protoclusters is shown in Fig 6, in black. The results from MacKenzie et al (2017) are also shown in magenta; this consists of 46 PHz sources (Planck Collaboration et al 2016c) with Herschel overdensities, likely in protoclusters. It can be seen that a significant fraction of our sources lie in the range 2 < z < 3, which is consistent with the expected peak of cosmic star-formation rate density either in protoclusters or in the field (Clements et al 2014;Madau & Dickinson 2014).…”
Section: Sed Fitting and Photometric Redshiftsmentioning
confidence: 95%
See 3 more Smart Citations
“…The photometric redshift distribution of all the sources in these 13 candidate protoclusters is shown in Fig 6, in black. The results from MacKenzie et al (2017) are also shown in magenta; this consists of 46 PHz sources (Planck Collaboration et al 2016c) with Herschel overdensities, likely in protoclusters. It can be seen that a significant fraction of our sources lie in the range 2 < z < 3, which is consistent with the expected peak of cosmic star-formation rate density either in protoclusters or in the field (Clements et al 2014;Madau & Dickinson 2014).…”
Section: Sed Fitting and Photometric Redshiftsmentioning
confidence: 95%
“…Nonetheless, a significant number of sources in our candidate protoclusters have infrared luminosities in the same range as the peak in PCL1002. Sources in MacKenzie et al (2017) tend to be more luminous. We conclude that the 850 µm sources in our candidate protoclusters are as luminous as those of known protoclusters (such as PCL1002), and have representitave infrared luminosities just below 10 13 L .…”
Section: Infrared Luminosities and Star-formation Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…The submillimetre (submm) window has become an important waveband for extragalatic astronomy due to the discovery of bright submm galaxies (SMGs). These galaxies appear to be among the earliest and most actively star-forming galaxies in the Universe, often reaching luminosities of more E-mail: rhliu@phas.ubc.ca than 10 13 L (over 100 times that of our Milky Way galaxy) and star-formation rates (SFRs) greater than a few hundred M yr −1 (e.g., Blain et al 2002;Magnelli et al 2012;Swinbank et al 2014;MacKenzie et al 2017;Micha lowski et al 2017) around redshifts 2-3, corresponding to only a few billion years after the Big Bang (e.g., Chapman et al 2005;Simpson et al 2014Simpson et al , 2017.…”
Section: Introductionmentioning
confidence: 99%